Big Data: Techniques and Technologies in Geoinformatics - Karimi, Hassan A. (CRC Press, 2014)
Big Data is defined as "a collection of data sets so large and complex that it becomes difficult to process using on-hand database management tools". The challenges include capture, storage, search, sharing, analysis, and visualization." Big Data has always been a major challenge in geoinformatics as geospatial databases are inherently very large. This book will integrate in one single volume techniques and technologies for storing and managing very large geospatial databases and help developing new geoinformatics software and systems that involve very large databases.